PEMANFAATAN MODELBUILDER UNTUK ANALISIS DAMPAK BENCANA KEBAKARAN PERKEBUNAN LAHAN SAWIT DI KABUPATEN ROKAN HULU TAHUN 2020 - Fahen Dayanda; Arie Yulfa (JURNAL BUANA, 2022)
This study aims to determine: 1) the distribution of fire locations in Rokan Hulu Regency in 2020. 2) fire area and the area of ​​burnt palm oil plantations in Rokan Hulu Regency in 2020. 3) the threat of forest and land fires using a 2020 modelbuilder analysis. This research is descriptive quantitative, which includes the distribution of fire locations, the threat of forest and land fires, and the area of ​​land fires and the area burned. The data analysis technique was carried out using Nearest Neighbor Analysis, Modelbuilder and Normalized Burn Ratio (NBR) and Difference Normalized Burn Ratio (dNBR). The results of the analysis found that Rokan Hulu Regency is an area that has the largest oil palm plantation in Riau Province, the threat of forest and land fires in Rokan Hulu Regency is 541,987,1 ha (74.51%) more than half of the administrative area, and high which has an area of ​​185401ha (25.49%), so the threat of forest and land fires is from moderate to high. The distribution of the number of hotspots (hotspots) in Rokan Hulu Regency is 56 hotspots (hotspots), the distribution of fire locations is clustered. The area of ​​fire for oil palm plantations in the North Tambusai sub-district is a very large affected area, namely 123,239 hectares. The least affected land plantation fire disaster is Ujung Batu, which is 12,332.5 Ha.